Leptin: a gender and obesity-related marker predictive of metabolic comorbidities and therapeutic response to anti-IL-23 biologic drugs in psoriatic patients - Belli, Roberta; Dattolo, Anna; Sampogna, Francesca; Gubinelli, Emanuela; Lulli, Daniela; Moretta, Gaia; Scala, Emanuele; Sanna, Luca; Megna, Matteo; Cannizzaro, Maria Vittoria; Parisi, Melania; Luordi, Cecilia; et al. (Frontiers in Immunology, 2025)
IntroductionPsoriasis is a chronic immune-mediated inflammatory skin disorder, frequently associated with comorbidities such as obesity, which can exacerbate its severity and hinder treatment efficacy. Psoriasis pathogenesis involves complex interactions among genetic, environmental, hormonal factors, and is characterized by dysregulated immune responses. In this study, we investigated the relationship between obesity and psoriasis, exploring the impact of circulating levels of adipokines on disease severity, comorbidities, and treatment response to anti-IL-17 and anti-IL-23 biologics.MethodsWe conducted an observational study that included 91 patients with psoriasis eligible for biological therapy, as well as 26 healthy controls. Disease severity was assessed using PASI, along with the measurement of body composition. Serum samples were analyzed for the measurement of adipokine levels and lipid profiles. Clinical parameters, bioelectrical impedance analysis (BIA), serum adipokine levels (leptin, visfatin, adiponectin) and lipid profile were assessed at baseline and after 16 weeks of biologic treatments.ResultsClinical parameters and adiposity-related indices were analyzed in 76 patients at both T0 and 16 weeks of anti-IL-17 and anti-IL-23 biological treatments, while serum adipokine levels were assessed in 66 patients. Psoriatic patients exhibited higher body mass index (BMI), waist circumference, fat mass (FM), and levels of visfatin (a pro-inflammatory adipokine), whereas adiponectin levels (an anti-inflammatory adipokine) were lower compared to controls. Circulating leptin (a pro-inflammatory adipokine) was significantly higher in female psoriatic patients and showed a positive correlation with the PASI score. Leptin also positively correlated with adiposity indices, while adiponectin showed negative correlations. Furthermore, in women, leptin levels were also associated with psoriatic arthritis, hypertension and, at lower extent, with type II diabetes. Finally, treatment with anti-IL-23 led to a reduction in visfatin levels in female psoriatic patients and resulted in a significant decrease in fat mass percentage in men. Notably, higher baseline leptin levels were associated with the failure to achieve an 90% improvement in baseline PASI at W16 of anti-IL-23 biologic treatments.ConclusionsThis study highlights significant sex-specific differences in the relationships between adipokines, body composition indices, psoriasis severity, comorbidities, and clinical outcome to therapies. Leptin, in particular, may serve as a predictive biomarker for response to anti-IL-23 therapies.